2010
DOI: 10.1242/dev.040568
|View full text |Cite
|
Sign up to set email alerts
|

COUP-TFs regulate eye development by controlling factors essential for optic vesicle morphogenesis

Abstract: SUMMARYTranscriptional networks, which are initiated by secreted proteins, cooperate with each other to orchestrate eye development. The establishment of dorsal/ventral polarity, especially dorsal specification in the optic vesicle, is poorly understood at a molecular and cellular level. Here, we show that COUP-TFI (Nr2f1) and COUP-TFII (Nr2f2) are highly expressed in the progenitor cells in the developing murine eye. Phenotype analysis of COUP-TFI and COUP-TFII single-gene conditional knockout mouse models su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 106 publications
(137 citation statements)
references
References 38 publications
7
127
2
1
Order By: Relevance
“…S14A). Because Coup-TF2 has overlapping functions with Coup-TF1 (Tang et al, 2010), we sensitized the Coup-TF2 mutants using a Coup-TF1 − allele. Mutants were generated using the following cross: Coup-TF1 +/− ; .…”
Section: Resultsmentioning
confidence: 99%
“…S14A). Because Coup-TF2 has overlapping functions with Coup-TF1 (Tang et al, 2010), we sensitized the Coup-TF2 mutants using a Coup-TF1 − allele. Mutants were generated using the following cross: Coup-TF1 +/− ; .…”
Section: Resultsmentioning
confidence: 99%
“…COUP-TFII (Nr2f2 -Mouse Genome Informatics), an orphan nuclear receptor, is essential for the morphogenesis of multiple organs (Takamoto et al, 2005a;Takamoto et al, 2005b;You et al, 2005a;You et al, 2005b;Kurihara et al, 2007;Petit et al, 2007;Li et al, 2009;Kim et al, 2009;Tang et al, 2010;Lin et al, 2010). In this study, we found that COUP-TFII was strongly expressed in the CGE, and we generated a conditional mutant that eliminated COUP-TFII function in the ventral telencephalon with RxCre.…”
Section: Introductionmentioning
confidence: 87%
“…hGFAP-Cre mice (Zhuo et al, 2001), Emx1-Cre (Gorski et al, 2002) and Nestin-CreER mice (Lagace et al, 2007) were obtained from the Jackson Laboratory. COUP-TFI flox/flox and COUP-TFII flox/flox mice were genotyped as previously described (Takamoto et al, 2005;Tang et al, 2010). Mice used in this study were of mixed background.…”
Section: Animals and Tissue Preparationmentioning
confidence: 99%